The effect of Green lea aqueous extract Camellia sinensisand Vitamin E in infertile men in Tikrit city and It’sSuburbs - Mohammad Mubark AL- Mahdawi, Zaid (Tikrit Journal of Pharmaceutical Sciences, 2023)
This study investigated the effects of Green tea aqueous extract and Vitamin I effect on the fertility of men, and the antioxidant and unti-infenile activity for comparison. The study included examination of (281) samples of seminal fluid of men thar were suffering from infertility caused by gonorrhea n :(144) , Varicose n: (47) , seminal vessels narrow 0: (31) , different inflammations n: (59) samples . and (60) samples from normal individuals (subjects) as a control, for the period from March(2008) 10 April(2009) in Tikrit city and its surrounding. The results appeared that adminstratio of green tea extract alone or with Vit. E in an infertile men (Gonorrhea infections, Varicocele |, Seminal vessels narrow and different sexual inflammations) lead to significant increase (p<0.03) in total numbers , the average of movement and normal forms of sperm. The treatment with Vit. k alone lead to increase in numbers and normal forms of spermatozoa , however , no significant variations were of served in the average of movement. The results indicated that using green tes agueous exirct , VitE or both logether were effective to inducing significant increase in the concentrations of testosterone hormone. In noma) cases the results showed no significant variation in total numbers of sperms after with preen tea extract or ViLE adminstration. whereas acminstration both together showed a significant increase , also an increase in the average of movement and normal forms when patints treated with green tea extract alone or green extract incombination with VitFE bu no significant variations were observed when treated with Vit.E alone The results emphasized that using Vit. E or green tea extract or both together were effective in inducing a significant increase in the concentration of lestosicrone hormone The causes of the green lea extract effectivness relate 10 its consistence of antioxidants which reduced the free mdicals in the infertile men and caused an improvement of their fertility.